Systematic review and meta-analysis of tuberculosis in animals in Nigeria - Ahmad, Ibrahim; Raji, Yakubu Egigogo; Hassan, Latiffah; Samaila, Abdullahi; Aliyu, Basiru; Zinsstag, Jakob; Fasina, Folorunso Oludayo (Elsevier BV, 2022)
Animal tuberculosis (TB) is a contagious and chronic disease caused by mycobacteria belonging to theMycobacterium tuberculosis complex (MTBC) in domestic and wild animals. MTBC strains infection has been confirmed in many animal species in Nigeria, including captive wildlife, cattle, dromedary camels, goats, and pigs. Despite widespread infection and the potential impact of the disease on public health, active surveillance and control strategies are absent in Nigeria. This study aimed to conduct the first comprehensive meta-analysis to assess the distribution of tuberculosis and analyze the potential moderators of infection in animals in Nigeria. Eligible studies (sixty-one (Cadmus et al., 2014) [61] prevalence and seven (Menzies and Neill, 2000) [7] case reports) were retrieved and included in the analysis. The analyses showed an overall pooled TB prevalence of 7.0% (95% CI: 6.0–8.0) comprising of infection distributed in cattle (8.0%, 95% CI: 7.0–8.0), goats (0.47%, 95% CI: 0–1.2), sheep (0.27%, 95% CI: 0.14–0.46), camels (13.0%, 95% CI: 0–47), and wildlife (13.0%, 95% CI: 9–16) respectively. The occurrence of infection was significantly moderated by the publication periods, geographical location, sample size, and detection methods. TB prevalence was heterogeneous across several predictors, with the year of publication exhibiting a higher rate (46%) of the detected heterogeneity. These findings should provide policy-relevant information to guide the design and establishment of prevention and control measures amenable to the local situations in Nigeria.